The knowledge and practice regarding disposal of waste insulin needles in patients with diabetes mellitus (糖尿病患者废弃胰岛素针头处理情况及相关因素分析) - LIU Huanhuan (刘欢欢); LIU Haiwei (刘海蔚); WU Yueli (吴月丽); ZENG Xiaocui (曾小翠); LIANG Changli (梁昌丽); LIANG Caiya (梁彩雅) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the knowledge and practice regarding disposal of waste insulin needles in patients with diabetes mellitus. Methods Using self-designed questionnaires to investigate the knowledge and practice regarding disposal of waste insulin needles in 307 inpatients with diabetes mellitus. Results The total scores of disposal of insulin needles was(6. 60±1. 51). Univariate analysis showed that history of diabetes、history of insulin injection、receiving instruction of disposal of insulin needles were related with knowledge of disposal of insulin needles(P＜0. 05). 38. 11%(117/307)of patients recapped and threw the used insulin needles into waste containers and brought to hospital when returning hospital. 25. 08%(77/307) of patients recapped and threw into special waste containers. Conclusion The behaviors of disposing used insulin needles was not optimistic and medical staff should strengthen the education of disposing waste insulin needles, and promote the management of the disposal. (目的 调查废弃胰岛素针头处理相关知识和行为的现状。方法 采用自行设计的废弃胰岛素针头处理知识和行为问卷对307例住院糖尿病患者调查。结果 废弃胰岛素针头处理知识总分为(6. 60±1. 51)分。单因素分析结果显示, 糖尿病病史、胰岛素注射史时长、是否接受过废弃胰岛素针头处理的教育与废弃胰岛素针头处理知识有关(P＜0. 05)。38. 11%(117/307)的患者将废弃胰岛素针头盖好外针帽放进废弃容器内, 复诊时带回医院统一处理。25. 08%(77/307)的患者盖外针帽放进专用废弃容器内再丢进垃圾桶。结论 糖尿病患者废弃胰岛素针头处理行为方面不容乐观, 医护人员应加强废弃胰岛素针头处理的教育, 促进对废弃胰岛素针头的妥善管理。)